Development of free and canal neuromasts and their directions of maximum sensitivity in the larvae of ayu,Plecoglossus altivelis - Mukai, Yukinori; Kobayashi, Hiroshi; Yoshikawa, Hiromasa (Springer, 1992)
Morphological changes in free neuromasts are reported from larvae of the Ayu,Plecoglossus altivelis. In newly-hatched larvae, free neuromasts were already recognizable in both the head and trunk. During larval growth, the number of free neuromasts increased, and the number of its sensory cells 2 days after hatching was constant. In the trunk, two types of free neuromasts, one with maximum sensitivity in the antero-posterior direction and the other with maximum sensitivity in the dorso-ventral direction, were observed. The former type predominated. In the head, free neuromasts were located around the eye and nose, their directions of maximum sensitivity forming lines tangential to concentric circles about the eye and nose. Distinct changes in free neuromasts occurred during the formation of the canal organ. The canal organ was first observed in the head region 64 days after hatching and in the trunk region 100 days after hatching. Concomitant with the formation of the canal organ, the profile of the cupulae of the free neuromasts changed from a flat bar to semispherical. Sensory cells in the canal neuromasts did not differ morphologically from those in the free neuromasts. It is considered that there is a close relationship between the sensitivity of the neuromast and the shape of the cupula, i.e., that the free neuromasts are adapted to slow water flow, as in lakes and the sea, while the neuromasts in the canal organ are adapted to rapid water flow.